Movements of neotropical forest deer: What do we know? - Grotta-Neto, Francisco [UNESP]; Barbanti Duarte, José Maurício [UNESP] (Springer Nature, 2019)
Neotropical forest deer comprise a range of species distributed in a wide variety of habitats. Due to that diversity, movement patterns studies of free-ranging deer are unequally distributed among the different species. Studies with Hippocamelus bisulcus examine altitudinal movements between seasons and in association with reproduction. H. bisulcus tend to select mid-slope habitats while avoiding the highest elevations. Furthermore, H. bisulcus move altitudinally and seasonally to find the best areas for foraging and in relation to reproductive cycles and social interactions. However, none of the population of H. bisulcus studied appears to migrate, which suggests that there is plenty of space and food to make migration unnecessary. Movement studies with Odocoileus virginianus have been conducted in Mexico. In the wet season, home range and daily distances were larger than dry season, which could be related to the intense search for best foraging places. Home ranges of female were smaller than males, and differences in distances covered per day were found between sex and seasons. For Mazama spp., movement patterns have been inferred from camera traps and radiotelemetry. M. bororo has been photographed most frequently along streams, and that behavior may be because traveling there is easy or it avoids predators. Home ranges for M. gouazoubira, M. bororo, and M. pandora were calculated in Bolivia, Brazil, and Mexico. Based on distance traveled and turning angles, movement patterns of M. gouazoubira in the Brazilian Pantanal were classified as encamped and exploratory, which were related to the type of habitat and period of day. Moreover, greatest distances moved found during the flooding season could be related to the availability of resources in areas that are not underwater and are separated by greater distances. Neotropical forest deer have been neglected in movement patterns studies, and the greatest challenges are associated with the difficulties to find efficient methods for capture and access to less costly telemetry equipment. Overcoming these barriers could further our understanding about the ecological roles the deer can play in the communities wherever they are found.
Keywords: Biotelemetry; Brocket deer; Cervidae; Elusive species; GPS collar; Movement behavior